Aesthetics, ethics and trauma in the cinema of Pedro Almodóvar - Gutiérrez-Albilla, Julián Daniel (Edinburgh University Press, 2017)
Reconceptualising AlmodÃ³Âđvar's films as theoretical and political resources, this innovative book examines a neglected aspect of his cinema: its engagement with the traumatic past, with subjective and collective memory, and with the ethical and political meanings that result from this engagement.